The relationship between near-space indices and weather conditions in İstanbul - Pekmezci, R. Gül Sevin. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2007., 2007)
The main subject occupying the scientists’ mind recently is the very reason of climate change. This question has to be immediately answered, because that change treats the existence of life on the Earth. Equal to the anthropogenic processes like high concentration of greenhouse gases emission, electromagnetic pollution, loss of forests and biodiversity, untreated disposals, and many more, the scientists think the near-space of Earth, especially the Sun is responsible for global warming as well. To detect any solar or cosmic signal on climate, local weather parameters are applied world-wide since they are not able to be measured globally. Due to this empirical approach, some of Istanbul’s meteorological data for almost one century like air temperature, air pressure, precipitation and wind velocity are investigated in order to find any possible coherencies with space indices like sunspot number, interplanetary magnetic field, geomagnetic activity and cosmic ray number. And it turned out that the Earth’s outer vicinity is not significantly responsible for the local weather of Istanbul, especially for the last three decades.
Keywords: Climatic changes -- Environmental aspects -- Turkey.; Climatic changes -- Turkey.